2013
DOI: 10.1159/000356631
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Properties of Galursan HF 7K on Mouse Gut Microbiota

Abstract: Background: With the rise of antibiotic resistance, new alternatives are being sought to effectively modulate the characteristics of gut microbiota to obtain pathogen resistance without the use of antibiotics. In the past, an oligosaccharide derivative of carrots, galursan HF 7K (GHF7K), has been used clinically in Austria and recently in the fowl-industry to promote health. This study examined the potential role of GHF7K as a prebiotic to alter the gut microbiota in mice. Methods: Mice were fed either a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…[1][2][3] In general, the gut microbiome consists of the major phyla Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, and Verrucomicrobia. 1,[4][5][6][7][8][9] The composition of these bacterial members varies along the length of the intestine. 4,6,10 Disruption of the normal microbiome structure has been associated with a number of intestinal disorders, including inflammatory bowel diseases (IBD), [11][12][13][14][15][16][17][18][19][20][21][22] irritable bowel syndrome (IBS), [23][24][25][26][27][28][29][30] obesity, [31][32][33][34][35][36][37][38][39] and enteric infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In general, the gut microbiome consists of the major phyla Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, and Verrucomicrobia. 1,[4][5][6][7][8][9] The composition of these bacterial members varies along the length of the intestine. 4,6,10 Disruption of the normal microbiome structure has been associated with a number of intestinal disorders, including inflammatory bowel diseases (IBD), [11][12][13][14][15][16][17][18][19][20][21][22] irritable bowel syndrome (IBS), [23][24][25][26][27][28][29][30] obesity, [31][32][33][34][35][36][37][38][39] and enteric infections.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that do focus on viral-induced changes in the microbiome rely largely on stool samples, which may not accurately reflect changes in the microbiome in the small intestine, a key site for chloride and water secretion that drive diarrhea. [4][5][6][52][53][54] Thus, further investigation is needed to understand how the small intestinal microbiome is altered following enteric viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodents have demonstrated that supplementation with fermentable dietary fiber in the diet can form a link between the result of microbial fermentation in the lower part of the intestine and the metabolic consequences, such as decreased food intake and WG, due to the beneficial modulation of secretion of intestinal peptide similar to glucagon1, glucose-dependent tropic insulin polypeptide, YY peptide, and/or ghrelin [19]. Other studies also did not observe a decrease in food intake or WG in rats with a weight considered healthy after prebiotic, supplementation in the diet [20,21], as well as in humans [22,23]. However, in obese or overweight rodents, prebiotics have been shown to assist in weight control by decreasing food intake [24].…”
Section: Discussionmentioning
confidence: 98%